Clinical and pharmaco-economical effectiveness of hospital-replacing technologies in cardiology - Ya. I. Kotz; M. V. Stolbova (Российский кардиологический журнал)
The study was aimed at determining heart pathology features in young and middle-aged patients with metabolic syndrome (MS). Ln total, 88 people aged 35-55 years, with various MS components, were examined. Seventeen patients had three MS components (Group 1), 42-4 components (Group 2), and 29-5 components (Group 3). Left ventricular (LV) electrical myocardial instability and autonomous dysfunction were observed in 16 %, cardiac arrhythmias - in 28 %, and ischemia -in 22 %. Metabolic disturbance severity directly correlated with the number of MS components. LV structure changes manifested in myocardial hypertrophy and increased myocardial mass (65 %), diastolic dysfunction (45 %), and systolic dysfunction (10 %). Therefore, young and middle-aged patients with various MS components demonstrated LV electrical myocardial instability, heart rate variability disorders, ischemic, structural and functional LV myocardial disturbances. These changes were more manifested in patients with more MS components.